Representasi Realita dan Nilai Pendidikan Karakter dalam Film Miracle In Cell No. 7 Versi Indonesia - Sylvi Purwihermawati; Taufik Arochman (UPA Bahasa Universitas Tidar And HISKI Kedu, 2026)
Nowadays, many people are less ethical because they surf the internet too much and watch shows that are less educational in character, but behind that there are films that contain moral values ​​and characters that are applied. One of the films that contain moral values ​​and characters is the film Miracle in Cell No. 7 (Indonesian Version), this film contains many positive messages and motivations for good behavior. Therefore, researchers are interested in analyzing what kind of moral messages are built in the film and knowing what kind of conflicts are built in the film so that they bring up a special message that is quite deep to the audience and the culture reflected in the film Miracle in Cell No. 7. Researchers use a qualitative approach which uses secondary data collection techniques obtained from documentation and literature sources. Researchers get the results of social problems in the film Miracle in Cell No. 7, namely poverty, discrimination, political issues, false accusations and coercion and acts of violence, and the culture reflected in the film Miracle in Cell No. 7, namely father and child affection, politeness, vigilantism, and religious tolerance. The film Miracle in Cell No. 7 contains many character education values ​​and several cultures that are worth emulating.